Análise da situação de trabalho do motorista em uma empresa de ônibus urbano da idade de Natal (RN) - Silveira, Ladijane Sarmento da (2011)
The problem dealt with in this study concerns the analysis of bus drivers' working situation. It stemmed from the need to identify the difficulties faced by these professionals in accomplishing the results expected by the company. A case study was carried out in a public transportation company in the city of Natal. Records and observations made in the workplace, alongside perfomance indicators, such as absenteeism tax, staff turnover and traffic accidents, revealed problems in their activity. It was made clear that, in the company being studied, absenteeism was related to health problems, particularly psychiatric and musculoskeletal disorders, and that although the indicators of traffic accidents and staff turnover have declined over the years, they are still elevated. The interviews involved 50 of the 124 drivers who worked directly in the service, and contained questions covering eleven factors related to the drivers' work. They indicated a gap between the prescribed work and the work actually done, in that there were a series of embarassing or stressful situations involving traffic, itinerary length, road conditions, vehicle maintenance, physical environment (bus terminus), job post and supervision policies. On the other hand, factors such as enjoying driving, the work itself and being with workmates positively influenced the drivers' working conditions. In the propositions of the administration and human resources subsystems, some alternatives were found in order to remodel this activity